The Effect of Depth, Frequency, and Stakeholder Engagement in Sustainability Reports on the Financial Performance of Service Companies in the Special Region of Jakarta - Akbar Tanjung; Nurul Afifah (Westscience Press, 2024)
This quantitative study investigates the relationship between sustainability reporting practices and financial performance among service companies operating in the Special Capital Region of Jakarta. The research examines the effects of depth, frequency, and stakeholder involvement in sustainability reports on financial performance metrics, using Structural Equation Modeling with Partial Least Squares (SEM-PLS) analysis. Data collected from 180 service companies are analyzed to assess the extent of sustainability reporting practices and their impact on financial performance. The findings reveal significant positive relationships between sustainability reporting practices and financial performance, highlighting the importance of robust sustainability reporting in enhancing organizational performance. The study contributes to both academic literature and practical insights by elucidating the mechanisms through which sustainability reporting practices can drive financial success in service companies.